2014
DOI: 10.1108/ijwbr-01-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tasting sheet sensory descriptors on tasting room sales

Abstract: To study the impact that tasting sheet sensory descriptors have on wine sales in tasting rooms that rely on direct-to-consumer sales to sell the majority of their wines, such as those in New York wine regions. o Design: Nine tasting rooms participated in the study that took place on weekends (Friday, Saturday, and Sunday) during a six-week period in July and August 2012. Tasting rooms alternated tasting sheets by weekend, one including sensory descriptors and one without any sensory descriptors. At the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…This finding is in line with a study of Spanish wineries showing that subjective notes/comments may no longer be a "must" to be included in a tasting sheet (Breit, 2013). This result is also consistent with a previous study by Thomas (2013) which found that objective sensory information may be more valuable and lead to higher sales in winery tasting rooms. This finding provides more nuanced evidence on the positive impacts of objective tasting descriptors on sales in winery tasting rooms.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This finding is in line with a study of Spanish wineries showing that subjective notes/comments may no longer be a "must" to be included in a tasting sheet (Breit, 2013). This result is also consistent with a previous study by Thomas (2013) which found that objective sensory information may be more valuable and lead to higher sales in winery tasting rooms. This finding provides more nuanced evidence on the positive impacts of objective tasting descriptors on sales in winery tasting rooms.…”
Section: Discussionsupporting
confidence: 93%
“…In tasting rooms, wine tasting guidance is offered by wine tasting notes/tasting sheets designed to supply information to help visitors find the wines that match their taste preferences. Tasting sheets are also used to suggest particular wines to consumers and to influence their purchase decisions (Thomas, 2013). Tasting sheets list comprehensive information about featured wines including sensory descriptors as well as supplemental information such as price, discounts, wine club membership offers, awards, and food pairings (Gómez & Kelley, 2013).…”
Section: Role Of Sensory Descriptors In Wine Salesmentioning
confidence: 99%
See 3 more Smart Citations